Participação dos sujeitos individuais na construção das políticas públicas em pequenos municípios: a experiência do município de Dois Irmãos - RS - Staudt, Tarcísio (Universidade do Vale do Rio dos Sinos, 2011)
The focus of this study was grounded in order to identify how participation and empowerment of the individual subjects influences the construction of public policies that strengthen citizenship and urban integration perceived by the social community. For forms that have been described, mechanisms and tools available in public discussion, they were characterized models of public policies that strengthen the participation of individual subjects premised on the interaction of social and urban integration of the transformation of the local area. In this sense, the survey was conducted in Dois Irmãos RS from the process of implementing the policy that public housing had its origin in the participation of individual subjects and social actors, the period being analyzed from 1988 to 2010. For comparability was conducted field research in parallel Tholey, State of Saarland, Germany, towards the identification of experience in public policy in small towns. Thus, the research has been characterized as descriptive and exploratory, in that the method used was observation and participation, based on specific case study, and data collected from documents and interviews with semi-structured questions were analyzed qualitatively. The results can be verified that the determination of individual subjects participation is linked to the political system adopted by the state, but public policies are influenced by individual subjects and these are agents of transformation of the site.
Keywords: Políticas públicas; Participação; Atores sociais; Sujeitos individuais; Public policy; Participation; Social actors; Individual subjects; ACCNPQ::Ciências Humanas::Sociologia